Foreign Bank Behavior during Financial Crises - Jonathon Adams-Kane; Julián Caballero; Jamus Lim (Inter-American Development Bank (IDB), 2014)
This paper studies whether lending by foreign banks is affected by financial crises. The paper pairs a bank-level dataset of foreign ownership with information on banking crises and examines whether the credit supply of majority foreignowned banks that underwent home-country crises differs systematically from that of other foreign banks. The baseline results show that banks exposed to homecountry crises in 2007 and 2008 exhibit changes in lending patterns that are lower by between 13 and 42 percent than their non-crisis counterparts. This finding is robust to potential alternative explanations and also holds, though less strongly, for the 1997-98 Asian crisis.
hdl:11319/6568
Keywords: G21; G01; F34; 330; Foreign bank ownership; Financial crisis; Bank lending